Laparoscopic partial nephrectomy for cancer: techniques and outcomes - Rubinstein,Mauricio (2005)
Open partial nephrectomy is the gold standard nephron-sparing treatment for small renal tumors. Technical aspects of laparoscopic partial nephrectomy have evolved considerably, and the technique is approaching established status at our institution. Over the past 4 years, the senior author has performed more than 400 laparoscopic partial nephrectomies at the Cleveland Clinic. Herein we present our current technique and review contemporary outcome data.